Analisis Willingness to Pay terhadap Iuran BPJS Kesehatan pada Pekerja Sektor Informal di Kota Semarang - Cindy Purnama Hardika; Evi Yulia Purwanti (Universitas Diponegoro, 2020)
National Health Insurance (JKN) aims to ensure the health of all citizens to fullfil the basic needs that are carried out by BPJS Kesehatan. However, every year BPJS Kesehatan has a deficit. This is caused by the mismatch between costs and benefits received, adverse selection, weak regulation in controlling the level of utilization, and the unoptimal level of collectivity that due to the low ability and willingness to pay (ability and willingness to pay). To cover the ongoing deficit, the government established a policy of increasing premium to reduce financial risk as an effort to maintain the sustainability of the BPJS Kesehatan. The purpose of this study is to analyze the factors that influence willingness to pay (WTP) BPJS Kesehatan contributions, the influence of the contribution increase policy on nursing class choices, and to identify costs that are willing to be paid against BPJS Kesehatan contributions. The method that is used in this study is the Contingent Valuation Method (CVM). Data was obtained through an individual survei of 100 informal sector workers who were Non Wage Recipient Participants (PBPU) in Semarang City. The average of willingness to pay (WTP) premium for BPJS Kesehatan of informal sector workers Semarang City is 50,190. The factors that influence a person's willingness to pay for BPJS Kesehatan premium are the level of income, quality of health services, knowledge about health insurance, the level of education, and the number of family.